2018
DOI: 10.1007/s12012-018-9457-z
|View full text |Cite
|
Sign up to set email alerts
|

Serum miR-30c Level Predicted Cardiotoxicity in Non-small Cell Lung Cancer Patients Treated with Bevacizumab

Abstract: Cardiotoxicity is a common adverse effect induced by drug chemotherapy. miR-30c has been reported to be involved in the progress of heart diseases. In the present study, miR-30c was used to predict the cardiotoxicity in non-small cell lung cancer (NSCLC) patients treated with bevacizumab chemotherapy. Eighty NSCLC patients were included in this study. Serum miR-30c levels were detected at pre-chemotherapy, during-chemotherapy (the 2nd, 4th, and 8th week) and 1 month after chemotherapy. miR-30c expression was e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…microRNA (miRNA) is a class of about 22 nucleotides conserved non-coding small RNA with the regulatory function, acting a pivotal part in the regulation of developmental timing, cell proliferation, and apoptosis as well as tumor development. Among all miRNAs, miR-30c-5p was served as a key regulator gene of multiple malignant tumors progressions, such as NSCLC [15], prostatic cancer [16] and esophageal squamous cell carcinoma [17]. Currently, many studies have manifested that miR-30c-5p, acts as a tumor suppressor gene, was inhibited cell proliferation and invasion through targeting SOX9 in human tumors [18, 19].…”
Section: Introductionmentioning
confidence: 99%
“…microRNA (miRNA) is a class of about 22 nucleotides conserved non-coding small RNA with the regulatory function, acting a pivotal part in the regulation of developmental timing, cell proliferation, and apoptosis as well as tumor development. Among all miRNAs, miR-30c-5p was served as a key regulator gene of multiple malignant tumors progressions, such as NSCLC [15], prostatic cancer [16] and esophageal squamous cell carcinoma [17]. Currently, many studies have manifested that miR-30c-5p, acts as a tumor suppressor gene, was inhibited cell proliferation and invasion through targeting SOX9 in human tumors [18, 19].…”
Section: Introductionmentioning
confidence: 99%
“…miR-30c expression was found correlated with duration of the chemotherapy cycle and decreased 1 month after chemotherapy. Moreover, correlation analysis showed that serum miR-30c levels were positively related to cardiotoxicity before chemotherapy and during chemotherapy [129].…”
Section: Mir-30 Familymentioning
confidence: 98%
“…This suggests that the specific elevations of miR1254 and miRNA579 may be the important indicators of BVZ-induced cardiotoxicity, allowing BVZ-induced cardiotoxicity to be distinguished from other cardiovascular disorders. Another research of patients with NSCLC receiving BVZ chemotherapy discovered that blood miR-30c expression rose with treatment duration and was positively correlated with cardiotoxicity before and during chemotherapy ( 180 ). According to a ROC curve investigation evaluating the area under curve sensitivity and specificity of changes in blood miR-30c levels, miR-30c may be a sensitive biomarker for diagnosing cardiotoxicity in patients with NSCLC treated with BVZ.…”
Section: Ncrnas As Biomarkers In Cancer Therapy-induced Cardiotoxicitymentioning
confidence: 99%